Shaping administrative activity (legal forms): a legislative approach - Hrubešová, Sára (Central European Public Administration Review, 2024)
Purpose: The topic of legal forms in public administration is strongly influenced by the principles of good administration. In the Czech legal order, the Parliament acts as the rule-maker of statutory foundations for public administration, making it crucial to focus on the legislative approach to enacting legal forms. This paper examines the weaknesses in legislation related to the enactment of legal forms of public administration, specifically through the principles of legal certainty and predictability of law. Design/Methodology/Approach: The author analyses Czech legal norms, existing legal doctrine, and administrative court’s rulings in relation to the legislative enactment of legal forms of public administration. This analysis leads to categorisation of legislative techniques based on the clarity with which the legal form of public administration activity is enacted. The paper also includes a case study consisting of a qualitative analysis of the legislative process in a specific case, based on publicly available records of parliamentary debates during the legislative process. Findings: In the case under review, there was no proper discussion of the implications of removing the explicit designation of legal form during the legislative process. No case has been found in which the Constitutional Court, acting as a negative legislator, annulled a statute for failing to explicitly specify a legal form, either due to its removal or its absence from the outset. Academic contribution to the field: The article highlights that, for the public administration to function effectively as good administration, the rules governing its activities must be clearly defined. The findings encourage legislators to ensure that proper discussions regarding the legal form of administrative activity take place when enacting laws. Such expert debate during the legislative process is essential to ensuring the clarity of the laws under which public administration operates in a particular legal form. Circumventing the legislative process or failing to engage in proper debate disproportionately impacts legal certainty and the predictability of law. Originality/Value: This article presents arguments emphasising the irrefutable role of the legislature in creating clear rules for the exercise of public administration and, as a direct result, enabling public administration to function as good administration. It points out the importance of clearly referencing the legal form of public administration in the law. The categorisation of legal form designation aids in identifying patterns and trends, helping to isolate relevant issues and focusing research on specific legal questions.
Keywords: administrative procedural rules; Constitutional Court; digitalno usmerjena zakonodaja; good administration; legal forms of public administration; legislative process; legislature; pravna država; pravna varnost; tehnološko nevtralno pravo; varuh človekovih pravic